Analysis of Factors Influencing the Financial Management Behavior of Medan City Students - Meigia Nidya Sari; An Suci Azzahra (International Journal of Management Research and Economics, 2025)
This research aims to find out how financial literacy and financial attitudes influence students' financial management behavior. Data collection was carried out by distributing questionnaires to 110 Medan City students to find out responses regarding the state of financial literacy, financial attitudes, and financial management behavior of students. Based on the results of the analysis, it shows that partially and simultaneously, the higher the financial literacy and financial attitude, the higher the student's financial management behavior. Students have relatively good behavior, indicating that students are able to apply the knowledge and attitudes they have to their financial management behavior. Optimizing financial literacy and attitudes is needed so that student behavior in managing finances becomes better in order to face increasingly complex financial problems.